A Project Designed by Cloud Storage Encryption Based on Separated Key - Zhizhong Wang; Cheng Zhou; Yufei Mou (Dianxin kexue)
The problems existing in the original cloud storage model has plagued the industry for many years, to realize the true sense of the data privatization in the static data encrypted storage process is able to ensure data security and protect data owners' interests. Cloud storage applications for the current secure storage of user data is able to improve data security. Taking Amazon S3 as an example, the general problem in static data security was analyzed. A new set of cloud static data encryption and storage solution, separated key S3, was designed, and a new key management method was also designed. The new technology absolutely accomplished the security of static data in the cloud. Additionally the data security analysis and prospect on next research was given.